The European Fish Hazard Index – An assessment tool for screening hazard of hydropower plants for fish. (February 2021) - van Treeck, Ruben; Radinger, Johannes; Noble, Richard A.A.; Geiger, Franz; Wolter, Christian
Graphical abstract: Abstract: Hydroelectricity is critical for decarbonizing global energy production, but hydropower plants affect rivers, disrupt their continuity, and threaten migrating fishes. This puts hydroelectricity production in conflict with efforts to protect threatened species and re-connect fragmented ecosystems. Assessing the impact of hydropower on fishes will support informed decision-making during planning, commissioning, and operation of hydropower facilities. Few methods estimate mortalities of single species passing through hydropower turbines, but no commonly agreed tool assesses hazards of hydropower plants for fish populations. The European Fish Hazard Index bridges this gap. This assessment tool for screening ecological risk considers constellation specific effects of plant design and operation, the sensitivity and mortality of fish species and overarching conservation and environmental development targets for a river. Further, it facilitates impact mitigation of new and existing hydropower plants of various types across Europe.